Hypo/unmethylated promoter status of Cdk2 gene correlates with its over-expression in ovarian cancer in north Indian population - Kanwal, A; Kaur, M; Singh, A; Gupta, S; Sachan, M (Cellular and Molecular Biology, 2016)
Cdk2 has been seen to play crucial roles in cell cycle regulation particularly in G1 to S phase transition and it is known to be involved in cancer progression and cancer cell proliferation. The aim of this study was to evaluate (i) the expression of cdk2 in malignancy of ovarian tumors and (ii) correlation between expression and DNA methylation. Clonal bisulfite sequencing and quantitative PCR analysis was performed for promoter methylation and expression analysis respectively in normal and ovarian tumor tissues. Increased methylation level was observed in normal ovarian tissues than ovarian carcinoma. An inverse relationship was found with expression levels of Cdk2 and DNA methylation.